Peran Budaya Organisasi Dan Manajemen Pengetahuan Terhadap Kinerja Aparatur - Alva A.G. Narande; Kasmir Kasmir (Manajerial, 2015)
This study was conducted in order to prove the hypothesis that has been formulated that there is significant influence of organizational culture dan knowledge management on the performance of the apparatus on the object of study, namely the Secretariat General of the Council of National Resilience. The study was conducted by using a quantitative approach in the form of a correlation study. Techniques of data collection using survey techniques through questionnaires, by giving a list of statements and questions to the 60 respondents as the sample is determined by means of simple random sampling. Conclusion the study proves that the influence of organizational culture on the performance of the apparatus Secretary General of Wantannas insignificant. While the influence of knowledge management on the performance of the Secretariat General Wantannas is significant. Similarly, studies have shown a significant influence of organizational culture and knowledge management simultaneous on the performance of the Secretariat General of Wantannas. Therefore, it is recommended that the Secretariat General of Wantannas develop organizational culture and knowledge management as one of the models of organizational coaching in improving the achievement of high performance